Community Service in 3R (Reduce, Reuse, and Recycle) Based Waste Management at RT 12, RW 04, Penurunan Subdistrict, Ratu Samban District, Bengkulu City - Antoni Saputra; Rahmat Renaldi; Ghandur Zhafran; Arif Nokra Median; Nadila Putri Wulandari; Sri Handayani; Lena Elfianty; Karona Cahya Susena (Universitas Dehasen Bengkulu, 2026)
The community service activity was conducted in RT 12 RW 04, Penurunan Subdistrict, Bengkulu City. One of the work programs implemented was the provision of organic and non-organic waste bins as an effort to improve environmental cleanliness and increase public awareness of waste management. This program aimed to encourage the community to separate waste according to its type and to reduce environmental pollution caused by improperly managed household waste. The methods used in this activity included direct observation and community participation through socialization activities and the provision of waste disposal facilities. The results of this program indicate a positive change in community behavior, as residents have begun disposing of waste according to its designated category. This program is expected to support the creation of a clean, healthy, and sustainable residential environment.